KECUAIAN PERUBATAN MENURUT UNDANG-UNDANG TORT DAN AUTORITI MENGENAINYA DARI SUDUT SYARIAH: Medical Negligence According To The Law of Tort And Its Authority From the Shariah - Ismail, Siti Zubaidah (Jurnal Syariah, 2011)
The tort system that is used to regulate the medical negligence litigation points out three main requirements in finding liability. Islamic legal tradition has also outlined the concept of negligence and medical negligence. The article examines the principles concerning medical negligence and the extension of doctor’s liability. When both tort and Islamic principles are juxtaposed, it shows that the Islamic principles and values can be adopted to underpin the tort system and this further proves that as a rule of law, Islamic law is adaptable to the modern scenario.